Effect of Product Quality and Price on Customer Loyalty through Customer Satisfaction at PT. Andaf Corporation - Putren, Irenne (Universitas Pamulang, 2023)
This study aims to determine the extent to which product quality and price influence customer loyalty through customer satisfaction at PT. Andaf Corporation. This research uses quantitative methods. The type of approach that researchers use is a type of quantitative description analysis approach with explanatory research. The research sample was taken using the probability sampling method from customers of PT. Andaf Corporation, totaling 26 samples. The findings of this study state that there is a significant direct effect between product quality and customer satisfaction. In addition, there is an effect of price on customer satisfaction, price on customer loyalty, price on customer loyalty, and customer satisfaction on customer loyalty, and there is an effect of product quality and price on customer loyalty through customer satisfaction. The results of this study are expected to provide benefits for the company and later can be an additional consideration for determining product quality and price.